2014
DOI: 10.25100/cm.v45i2.1479
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic stimulation as coadjuvant in the healing of diaphyseal femoral fractures: a randomized controlled trial

Abstract: Introduction: There is controversy in medical literature regarding the use of electromagnetic fields to promote bone healing. Methods: After designing and building devices capable of generating an electromagnetic field for this study, their safety was confirmed and the electromagnetic therapy was randomly allocated and compared to placebo in patients with fracture of the femoral diaphysis. Treatment began six weeks after the fracture and it was administered once a day, during 1 h, for eight consecutive weeks.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 16 publications
1
37
0
Order By: Relevance
“…hour was sufficient to induce fracture healing [109]. In line with this, the study of Cheing et al showed that 30 minutes ELF-PEMF (∆tb = n.s.…”
Section: Elf-pemf Treatment To Support Acute Fracture Healingmentioning
confidence: 71%
See 4 more Smart Citations
“…hour was sufficient to induce fracture healing [109]. In line with this, the study of Cheing et al showed that 30 minutes ELF-PEMF (∆tb = n.s.…”
Section: Elf-pemf Treatment To Support Acute Fracture Healingmentioning
confidence: 71%
“…Strongest effects were observed with an ELF-PEMF treatment of 75 Hz applied for ≥8 h per day for 90 days [108], however, it is not clear whether this effect is attributed to the higher frequency, other specific ELF-PEMF characteristics, and/or the higher age. Interestingly, solid results were observed when applying the ELF-PEMF with a range of frequencies-with this ELF-PEMF, a daily exposure of 1 h was sufficient to induce fracture healing [109]. In line with this, the study of Cheing et al showed that 30 min ELF-PEMF (∆t b = n.s.…”
Section: Elf-pemf Treatment To Support Acute Fracture Healingmentioning
confidence: 79%
See 3 more Smart Citations